Adaptation and Validation of a Scale for Measuring the Curriculum-Based Professional Learning Community in Early Childhood Education in China - Qian Peng; Lijia Liu; Limin Zhang; Yaping Yue (Frontiers in Psychology, 2022)
Teachers' professional learning community, as an effective path to promote teachers' professional development and elevate teaching quality, has been widely used in school contexts. In preschools, the practice of teachers' professional learning community mainly focuses on the curriculum in early childhood education. The revision and adaptation of the scale of the professional learning community for preschool teachers in the Chinese cultural context are of great significance for understanding the current situation of the professional learning community for preschool teachers and improving the quality of collaboration within the community. Teachers' Professional Learning Community scale was revised into the Curriculum-Based Professional Learning Community scale according to the characteristics of the curriculum in early childhood education in the Chinese context. Based on the data from a sample of 2,823 teachers, the study conducted an item analysis and exploratory factor analysis (EFA) on participants from sample A (N = 1,410) and confirmatory factor analyses (CFAs) on participants from sample B (N = 1, 413). Short-form Teacher Self-Efficacy scale was used as the criteria-related validity instrument. Sample A and sample B were used to explore the relationship between various dimensions of teachers' professional learning community and teachers' teaching efficacy. The results showed that instead of the five-factor structure of the original PLC scale, the Chinese version of the CBPLC scale consists of four factors: Shared Sense of Purpose, Collective Focus on Children Learning and Development, Collaborative and Reflective Activity, and Deprivatized Practice. The revised scale has high reliability and validity and can be used as an effective tool to measure the curriculum-based professional learning community of preschool teachers in China. The results of CFA indicated that the four-factor CFA model fit the data well, and the CBPLC significantly and positively predicted teachers' self-efficacy including instructional strategies, students' engagement, and classroom management.